For Contributors to This Collection, "Public" Is the Defining Identity - Jay Lamar (The University of Alabama, 2022)
Review of the book: Katharyne Mitchell, editor, Practising Public Scholarship: Experience and Possibilities Beyond the Academy, West Sussex: Wiley-Blackwell, 2008, 152 pages. ISBN: 978-1-4051-8912-5